INCORPORATING MORINGA AND KATUK LEAF EXTRACTS IN THE PRODUCTION OF SAGO BASED LIQUID SUGAR: SENSORY PROPERTIES, GLUCOSE CONTENT AND ANTIOXIDANT ACTIVITY - Ansharullah, Ansharullah; Natsir, Muhammad; tamrin, tamrin; Asranudin, Asranudin (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2019)
ABSTRACT Incorporation of the extracts of Moringa and Katuk leaves in the production of sago based liquid sugar was one way to diversify and improved its added value. The liquid sugar produced had a better anti-oxidant activity, but had a lower sensory properties. A pilot plant scale production of this liquid sugar was attempted in collaboration with a small scale enterprise in Moramo,Southeast Sulawesi. This study was aimed to determine the fortification effect of Moringa and Katuk leaf extract on the properties of sensory, and anti-oxidant activity of the sago liquid sugar. The sugar was produced enzymatically through liquefaction and saccharification processes employing commercial alfa-amylase and amyloglucosidase. The sugar was then fortified with the extract of Moringa and Katuk leaves, with various concentrations, i.e. G0 (100 % liquid sugar as a control); G1 (95% liquid sugar + 5% Katuk extract), G2 (95% liquid sugar + 5% Moringa extract), G3 (90% liquid sugar + 5% Moringa extract + 5% Katuk extract), G4 (85% liquid sugar + 5% Moringa extract + 10% Katuk extract), and G5 (85% liquid sugar + 10% Moringa extract + 5% Katuk extract). The results showed that fortification of Moringa and Katuk leaf extract had a significant effect on the sensory properties, and anti-oxidant activity. The G1 treatment produced better sensory properties. Increasing the content of leaves extracts had also increased the anti-oxidant activity. There was no significant differences in the glucose content of the sugar. Considering various aspects of the results obtained, the G3 formula was then scaled up for pilot plant production by a small scale enterprise. This study had indicated that a nutritional food ingredients and added value may be made through a diversified process of sago flour. Keywords: Moringa, katuk, sago liquid sugar, anti-oxidant, sensory properties INTRODUCTION The use of sago as a food has long been recognized and has even become